The Neutrophil-to-Lymphocyte Ratio (NLR) and suicidal ideation: A potential inflammatory indicator in affective disorders - Wirasto, Ronny Tri; Arganist, Maharani Primastuti (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Background: Inflammation is increasingly recognized as a key factor in the pathophysiology of mental disorders, including affective disorders. Evidence suggests that elevated inflammation markers may be associated with a higher risk of suicidal ideation in patients with conditions such as depression and bipolar disorder. Cost-effective and accessible biomarkers are needed to identify individuals at high risk. The Neutrophil-to-Lymphocyte Ratio (NLR) is an easily obtainable inflammatory biomarker that may serve as a predictor of suicidal ideation in this population.Objectives: To evaluate the predictive performance of NLR for suicidal ideation in patients with affective disorders. Methods: A cross-sectional, retrospective study was conducted using secondary data from medical records of inpatients at Dr. Sardjito General Hospital, Yogyakarta, between January and December 2023. Eighty patients diagnosed with affective disorders were selected through consecutive sampling based on predefined inclusion and exclusion criteria. Participants were classified into two groups: those with suicidal ideation and those without. Categorical variables were comparedusing the Chi-square test and numerical variables analyzed using the Mann–Whitney U test or independent t-test, as appropriate. Receiver Operating Characteristic (ROC) curve analysis was performed to assess the predictive performance of NLR, with the Area Under the Curve (AUC), sensitivity, specificity, and optimal cut-off values reported. Results: The mean NLR was significantly higher in patients with suicidal ideation (3.55) than in those without (2.46)(p=<0.001). ROC curve analysis yielded an AUC value of 0.783 (p=<0.001). The optimal cut-off for NLR was 2.77, with a sensitivity of 72.5%,specificity of 72.5%, and accuracy of 72.5%. An odds ratio of 6.95 (95% CI) was observed, indicating a significant association between elevated NLR and suicidal ideation.Conclusion: A relationship exists between NLR and suicidal ideation in patients with affective disorders.